Difficulties and Discontents of Decisions of Senior Pupils - Jatautaitė, Birutė (Acta Paedagogica Vilnensia, 1993)
The stability, dynamism and success of vocational choice, professional development of a personality is influenced by many factors: social, economic, psychological, health related, educational, etc. Based on these factors of vocational choice, career guidance system should prepare young people for optimal and conscious choice, so that the individual's needs, talents, interests, values, life plans correspond with the requirements of their chosen profession. However, the surveys of the IX and XII grade students showed that the life plans of the students of these classes are only beginning to take shape, and are often contradictory. The problem of instability of professional intentions is very clear. When choosing a profession many ninth-graders are directed not by their individual mental characteristics, but more by specifically defined social values, such as “to do good for people, bring benefits to the people” and so on. Twelfth-graders don’t show much self-analysis and self-knowledge either. The survey also revealed the following trends: a large workload does not encourage students to pursue higher achievement required to obtain entry to the desired profession; a number of students do not have formed skills of a planned, creative work; good learning and abilities in many areas also hinders decision, in particular when lacking self-knowledge.
Keywords: vocational guidance; vocational self-determination; self-awareness; vocational counselling